Technological Advancements in Retail Kiosks: Enhancing Operational Efficiency and Consumer Engagement - Sachani, Dipakkumar Kanubhai (American Journal of Trade and Policy, 2018)
This study investigates how technology innovations in retail kiosks affect operational effectiveness and customer engagement. The primary goals were to assess new developments in retail kiosk technology, look at how kiosks affect both customer engagement and operational effectiveness, pinpoint opportunities and problems with kiosk integration, and suggest policy changes to optimize the advantages of retail kiosks. The methodology comprised a thorough investigation of academic and industry sources and a review of case studies and literature on retail kiosk technology. Key findings show that sophisticated technologies like augmented reality and artificial intelligence are becoming more thoroughly integrated into retail kiosks, improving consumer engagement and operational efficiency. However, obstacles, including integration problems and data security issues, must be resolved to utilize retail kiosks properly. The policy implications include encouraging interoperability standards, giving equal access to retail kiosk technology, and giving priority to data protection laws. Technology developments in retail kiosks present enormous potential to change the retail environment and give customers engaging, customized shopping experiences.
Keywords: Retail Kiosks; Operational Efficiency; Consumer Engagement; Smart Kiosks; Retail Technology; Interactive Kiosks; Digital Transformation; Technological Advancements